2019
DOI: 10.7717/peerj.7995
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of NAC transcription factors in Gossypium barbadense uncovers their roles in response to Verticillium wilt

Abstract: As one of the largest plant-specific gene families, the NAC transcription factor gene family plays important roles in various plant physiological processes that are related to plant development, hormone signaling, and biotic and abiotic stresses. However, systematic investigation of the NAC gene family in sea-island cotton (Gossypium babardense L.) has not been reported, to date. The recent release of the complete genome sequence of sea-island cotton allowed us to perform systematic analyses of G. babardense N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
(92 reference statements)
3
12
0
Order By: Relevance
“…This expansion might arise from multiple gene duplication events, including whole-genome duplication in the Arachis lineage followed by multiple segmental and tandem duplication events [ 27 , 32 ]. These results were identical to those NAC from cultivated cotton Gossypium barbadense and two diploid cotton species, Gossypium rainondii and Gossypium arboreum [ 45 ]. Previous studies revealed that the involvement of NAC genes performed major functions in transcription regulation [ 45 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This expansion might arise from multiple gene duplication events, including whole-genome duplication in the Arachis lineage followed by multiple segmental and tandem duplication events [ 27 , 32 ]. These results were identical to those NAC from cultivated cotton Gossypium barbadense and two diploid cotton species, Gossypium rainondii and Gossypium arboreum [ 45 ]. Previous studies revealed that the involvement of NAC genes performed major functions in transcription regulation [ 45 ].…”
Section: Discussionsupporting
confidence: 86%
“…These results were identical to those NAC from cultivated cotton Gossypium barbadense and two diploid cotton species, Gossypium rainondii and Gossypium arboreum [45]. Previous studies revealed that the involvement of NAC genes performed major functions in transcription regulation [45]. Thus, we speculated that NACs might perform functions through regulating stress-resistant-related genes or proteins, while not performing functions like a "on-off" switch.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the transcription levels of duplicated BdGATA gene pairs exhibited similar expression patterns, indicating that their role could be redundant. The functional redundancy of duplicated genes may be associated with the analogous CREs, gene models, and conserved motifs [ 38 ]. For instance, BdGATA7/19 duplicated pairs showed similar tertiary structures and expression patterns in response to M. oryzae inoculation, and both are predicted to interact with MBF proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For Instance, 13 WRKY genes were identified on each of re-constructed G. arboreum A_A12 and G. raimondii D_D08 chromosomes with high collinearity. Recent study also reported highly conserved collinearity among TF-related genes of four Gossypium species [65]. In contrast, another study using previously assembled G. arboreum genome [27] identified different number of WRKY genes and their unobvious collinearity in G. arboreum and G. raimondii chromosomes 12, respectively [63].…”
Section: Discussionmentioning
confidence: 99%